Ammonite faunas and stratigraphy of the Lower Bajocian of Paso del Espinacito (Middle Jurassic, San Juan Province, Argentina) - Dietze, Volker (2010)
The classical outcrop of the Paso del Espinacito (San Juan Province, Argentina), wherefrom GOTTSCHE (1878) and TORNQUIST (1898) described many Early Bajocian ammonite species – some of them later became type species of new genera – was restudied by one of us (A. v. H.) in 1968. The newly collected ammonites sampled bed-by-bed are described and illustrated. The fi nds of many topotypes for most of the GOTTSCHE and TORNQUIST taxa allows a reconstruction of their type horizons. The strata are subdivided in the standard chronozones of the Andean Province: the Puchenquia malarguensis Zone in the Aalenian and the Pseudotoites singularis and Chondromileia giebeli zones in the Lower Bajocian. The Singularis Zone is subdivided into two new subzones: the Fissilobiceras zitteli Subzone in the lower part with the Pseudotoites singularis horizon and the Sonninia altecostata Subzone in the upper part with the Pseudotoites sphaeroceroides horizon. The Giebeli Zone is subdivided into their standard subzones: the Chondromileia submicrostoma Subzone with the horizon of Ch. submicrostoma and the Emileia multiformis Subzone with the Ch. giebeli horizon. These zones and subzones of the Andean Province are tentatively correlated with the standard zones of the Northwest-European Province.